2016
DOI: 10.1093/jamia/ocv200
|View full text |Cite
|
Sign up to set email alerts
|

Automatic detection of social rhythms in bipolar disorder

Abstract: Automatic smartphone sensing is a feasible approach for inferring rhythmicity, a key marker of wellbeing for individuals with BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
200
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 198 publications
(205 citation statements)
references
References 20 publications
2
200
1
2
Order By: Relevance
“…Only two studies have investigated Activity for clinical samples of patients; Beiwinkel et al [21] reported a negative correlation in a between-subject analysis, but the within subject analysis that we reported on had almost zero correlation (r = .02, p = .87), and we reported on Abdullah et al [54] weighting coefficient as the correlation direction (w = 3.79x10 4 ). Distance was analyzed in the same two studies, again with an almost zero correlation by Beiwinkel et al [21] (r = .03, p = .66).…”
Section: Clinical Samples Of Patients Diagnosed With Ud or Bdcontrasting
confidence: 47%
See 1 more Smart Citation
“…Only two studies have investigated Activity for clinical samples of patients; Beiwinkel et al [21] reported a negative correlation in a between-subject analysis, but the within subject analysis that we reported on had almost zero correlation (r = .02, p = .87), and we reported on Abdullah et al [54] weighting coefficient as the correlation direction (w = 3.79x10 4 ). Distance was analyzed in the same two studies, again with an almost zero correlation by Beiwinkel et al [21] (r = .03, p = .66).…”
Section: Clinical Samples Of Patients Diagnosed With Ud or Bdcontrasting
confidence: 47%
“…In a study where Muaremi et al [60] used microphone features to classify mood, they achieved an F1 accuracy of 82%, and discovered speaking time as the best-performing feature. By expanding to include GPS and accelerometer-related features, Abdullah et al [54] achieved an F1 accuracy of 85.5% with the GPS feature: Distance achieving largest weighting. The same F1 accuracy was achieved by Palmius et al [62] who used 50 location based features from GPS, WIFI, and GSM cell tower ID.…”
Section: Feature Combined Modelsmentioning
confidence: 99%
“…Abdullah et al [9] reported that combining self-reported data with data from several smartphone sensors and communication patterns resulted in reliable prediction of Social Rhythm Metric, a clinically-validated marker of stability and rhythmicity for individuals with bipolar disorder. A different study [10] collected voice features that were automatically generated using smartphones from 28 outpatients on a daily basis during a period of 12 weeks.…”
Section: The Monitoring Of Activity Of Daily Living and Episodic Epismentioning
confidence: 99%
“…The normal use of a smartphone on a daily basis generates a larger amount of data than the amount that is typically collected in questionnaire-based studies or online interventions. Smartphone sensor-based analysis already showed interesting results assessing bipolar disorder [9], depression symptoms [6] and sleep duration [18]. In this work, we proposed a preliminary assessment of a method for patients with mental health conditions.…”
Section: Future Applicationmentioning
confidence: 99%
“…HCI research has recently started to focus on how technology can support psychological wellbeing [e.g. 1,21,78]. The growth in use and sophistication of mobile health (mHealth) apps for mental health presents particular opportunities and challenges for design [22,83].…”
Section: Introductionmentioning
confidence: 99%